Implementing community-based provider participation in research: an empirical study - Teal Randall; Bergmire Dawn M; Johnston Matthew; Weiner Bryan J (Implementation Science, 2012)
Abstract Background Since 2003, the United States National Institutes of Health (NIH) has sought to restructure the clinical research enterprise in the United States by promoting collaborative research partnerships between academically-based investigators and community-based physicians. By increasing community-based provider participation in research (CBPPR), the NIH seeks to advance the science of discovery by conducting research in clinical settings where most people get their care, and accelerate the translation of research results into everyday clinical practice. Although CBPPR is seen as a promising strategy for promoting the use of evidence-based clinical services in community practice settings, few empirical studies have examined the organizational factors that facilitate or hinder the implementation of CBPPR. The purpose of this study is to explore the organizational start-up and early implementation of CBPPR in community-based practice. Methods We used longitudinal, case study research methods and an organizational model of innovation implementation to theoretically guide our study. Our sample consisted of three community practice settings that recently joined the National Cancer Institute’s (NCI) Community Clinical Oncology Program (CCOP) in the United States. Data were gathered through site visits, telephone interviews, and archival documents from January 2008 to May 2011. Results The organizational model for innovation implementation was useful in identifying and investigating the organizational factors influencing start-up and early implementation of CBPPR in CCOP organizations. In general, the three CCOP organizations varied in the extent to which they achieved consistency in CBPPR over time and across physicians. All three CCOP organizations demonstrated mixed levels of organizational readiness for change. Hospital management support and resource availability were limited across CCOP organizations early on, although they improved in one CCOP organization. As a result of weak IPPs, all three CCOPs created a weak implementation climate. Patient accrual became concentrated over time among those groups of physicians for whom CBPPR exhibited a strong innovation-values fit. Several external factors influenced innovation use, complicating and enriching our intra-organizational model of innovation implementation. Conclusion Our results contribute to the limited body of research on the implementation of CBPPR. They inform policy discussions about increasing and sustaining community clinician involvement in clinical research and expand on theory about organizational determinants of implementation effectiveness.